Effect of Bioentrepreneurship on Biology Learning Achievement, Creativity, and Entrepreneurial Interest (Journal of Innovative Science Education, 2020)
Indonesia is the second-largest plastic waste producer in the world. This situation provides an entrepreneurship opportunity to process plastic wastes into useful and valuable goods.The integration of two different disciplines science, biology and entrepreneurship, is called bio-entrepreneurship (BEP). The aims of this study were 1) to describe BEP implementation in the learning topic of Environmental Changes at Senior High School (SHS) 3 Slawi, 2) to analyze the effect of BEP implementation on students’ learning achievement, 3) to analyze the effect of BEP implementation on students’ creativity, 4) to analyze the effect of BEP implementation on students’ entrepreneurial interests. BEP was implemented on the Environmental Change topic at SHS 3 Slawi. The population in this study were all 10th-grade students and the sample was fifth tenth-grade science students. The study design used was Time Series Design with one group. Findings showed that there were increases in students learning achievement, creativity, and entrepreneurial interest. BEP had a positive effect on improving biology learning achievement, creativity, and entrepreneurial interest. BEP was also suitable for biology learning to increase learning achievement, creativity, and entrepreneurial interest